Determination of Bromhexine HCl, Dextromethorphan HBr, Chlorpeniramine Maleate in Sedosolvin Suspension - Lokhande, R.S.; Wabgaonkar, Swati; Patil, Dhanaji (Asian Journal of Chemistry, 2010)
A simple, fast and accurate high performance liquid chromatographic method has been developed for the determination of bromhexine HCl, dextromethorphan HBr, chlorpeniramine maleate in sedosolvin suspension. Sedosolvin suspension contains bromhexine HCl a mucolytic, dextromethorphan HBr a cough suppressant and chlorpheniramine maleate which is an antiallergic drug. Sedosolvin suspension is indicated for dry cough. The low values of standard deviation and coefficient of variation indicate high precision of the method. The average recovery was found to be within pharmacopoeial limits.